The Effect of Moral Foundations on Intergroup Relations: The Salience of Fairness Promotes the Acceptance of Minority Groups - Argüello-Gutiérrez, Catalina; López-Rodríguez, Lucía; Vázquez, Alexandra (Social Psychological and Personality Science, 2023)
Previous research suggests that moral foundations have consequences for intergroup relations, but the evidence is mostly correlational and gathered mainly in north American countries. This work aimed to replicate the conceptual findings in the European context and test the effects of manipulating a moral framing on the perceived (im)morality of minority groups, willingness to defend their rights collectively and support for anti-immigration policies. A correlational study showed that binding and individualizing foundations contributed to predict support for anti-immigration policies and willingness to participate in collective actions for immigrants’ rights. A follow-up experiment suggested that emphasizing the benefits for society of fairness—an individualizing foundation—(vs. authority—a binding foundation) may improve intergroup evaluations, increase collective action intentions, and reduce support for anti-immigration policies. Although a second preregistered experiment could not replicate the results, complementary analyses suggested some positive effects of fairness compared with the control and authority conditions. These results open a path to investigate whether a fairness moral reasoning might improve attitudes toward immigrants.
Keywords: anti-immigration policies; collective action; intergroup attitudes; moral foundations; Scopus; JCR